First-principles insights into the electronic and magnetic structure of hybrid organic-metal interfaces - Lazić, Predrag; Caciuc, Vasile; Atodiresei, Nicolae; Callsen, Martin; Blügel, Stefan (Journal of physics. Condensed matter, 2014)
In this review we summarize our experience gained from several recent ab initio studies aimed to investigate how the competition between short-ranged chemical and long-ranged dispersion interactions determines the bonding mechanism of a specific set of chemically functionalized π-conjugated organic molecules on non-magnetic and magnetic metal surfaces. A key point of this review is to provide a detailed analysis on the issue of how to tune the strength of the organic molecule-surface interaction, such that the nature of the molecular bonding exhibits the specific electronic features of the physisorption or chemisorption bonding mechanisms. In particular, we discuss in detail how the precise control of these bonding mechanisms can be used to design specific electronic and magnetic properties of hybrid organic-metallic interfaces. Furthermore, our first-principles simulations provide not only the basic insights needed to interpret surface-science experiments, but are also a key tool to design organic-substrate systems with tailored properties that can be integrated into future organic-based devices for molecular electronics and molecular spintronics applications.